Association Mapping Reveals Novel Stem Rust Resistance Loci in Durum Wheat at the Seedling Stage. Issue 1 (1st March 2014) - Letta, Tesfaye; Olivera, Pablo; Maccaferri, Marco; Jin, Yue; Ammar, Karim; Badebo, Ayele; Salvi, Silvio; Noli, Enrico; Crossa, Jose; Tuberosa, Roberto
Abstract : Wheat stem rust rapidly evolves new virulence to resistance genes. Recently emerged races in East Africa, such as TTKSK (or Ug99), possess broad virulence to durum cultivars, and only a limited number of genes provide resistance. An association mapping (AM) study conducted on 183 durum wheat accessions has allowed us to identify 41 quantitative trait loci (QTLs; determination coefficient [ R 2 ] values from 1.1 to 23.1%) for seedling resistance to one or more of four highly virulent stem rust races: TRTTF, TTTTF, TTKSK (Ug99), and JRCQC, two of which (TRTTF and JRCQC) were isolated from Ethiopia. Among these loci, 24 are novel, while the remaining 17 overlapped with loci previously shown to provide field resistance in Ethiopia and/or chromosome regions known to harbor designated stem rust resistance designated loci ( Sr ). The identified loci were either effective against multiple races or race specific, particularly for race JRCQC. Our results highlight that stem rust resistance in durum wheat is governed in part by loci for resistance across multiple races, and in part by race‐specific ones (23 and 18, respectively). Collectively, these results provide useful information to improve the effectiveness of marker‐assisted selection towards the release of durum wheat cultivars with durable stem rust resistance.